A 2‐year prospective follow‐up study of temporal changes associated with post‐stroke cognitive impairment. Issue 2 (1st January 2018) - Oh, HyunSoo; Park, JongSuk; Seo, WhaSook
Abstract: Aims: To explore temporal patterns of change in cognitive impairments during the 2 years following stroke and to identify factors that affect these temporal changes. Background: Despite the prognostic importance, temporal changes in post‐stroke cognitive impairment have not been systematically investigated. Design: A non‐experimental, prospective, longitudinal descriptive study design. Methods: Fifty‐two stroke patients were enrolled. Data were collected from April 2015 to September 2017. Cognitive function was evaluated at 5 different times (immediately, and at 3, 6, 12, and 24 months post‐stroke). Results: Significant changes in cognitive function following stroke exhibited an "s‐shaped" curve, and the most rapid changes were observed between 3 and 6 months after stroke. The incidence of post‐stroke cognitive impairment ranged from 23.1% to 42.3% and was highest at 3 months and lowest at 6 months. Gender, educational level, pre‐stroke cognitive and functional abilities, haematoma, and brain surgery were associated with incidence of post‐stroke cognitive impairment. Conclusions: The ongoing changes exhibited by patterns of cognitive impairment provide evidence that consistent efforts are required to achieve positive changes in post‐stroke cognitive function. Our findings may be helpful to develop nursing care strategies aimed at improving cognitive ability and consequently the quality of life of stroke patients. SUMMARY STATEMENT: What is already known about this topic? Post‐stroke cognitive impairment (PSCI) is among the most common complications that cause stroke patients to be dependent on others. Despite the prognostic importance of PSCI in stroke patients, temporal changes in PSCI have not been systematically investigated. What this paper adds? Cognitive function changes significant throughout the 2 years following stroke, and the most dynamic changes in PSCI were observed between 3 and 6 months after stroke. The incidence of PSCI ranged from 23.1% to 42.3% and was highest at 3 months and lowest at 6 months after stroke. The factors found to be associated with PSCI incidence were gender, educational level, pre‐stroke cognitive and functional abilities, presence of haematoma at admission, and brain surgery. The implications of this paper: The continual changes in PSCI patterns caution that constant efforts should be made by patients, families, and nurses to achieve positive changes in patients with PSCI. The findings of this study may be helpful to develop nursing care strategies aimed at improving cognitive ability and consequently the quality of life of PSCI patients.